Pengaruh Penerapan Fitur Promosi Shopee terhadap Penjualan Produk Nata De Aloe Vera - Mustofa, Imam Mujahidin; Rimartin , Geraldo Adinugra; Sadiyah, Fitria Naimatu (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
Shopee serves as a vital digital marketplace for small and medium-sized enterprises (SMEs) like PT Mount Vera Sejati, facilitating the online promotion of their Nata De Aloe Vera products. However, the intense competition from numerous similar products poses significant marketing challenges. This study aims to examine the implementation of Shopee’s promotional features on PT Mount Vera Sejati’s account and analyze the impact of each feature on sales performance. The features investigated include Free Shipping, Vouchers, Discounts, Flash Sales, Product Search Ads, and Similar Product Ads. Utilizing a quantitative descriptive methodology, data were collected from daily sales records between December 2024 and March 2025, complemented by observations and interviews with the business owner. The analysis reveals that Free Shipping, Discounts, and Vouchers are the most effective promotional tools, collectively facilitating the sale of 72 units during the 58-day observation period. Specifically, Free Shipping accounted for 70 sales, Discounts for 38 sales, and Vouchers for 72 sales. In contrast, Flash Sales and product advertisements showed limited effectiveness. These findings highlight the necessity for PT Mount Vera Sejati to prioritize and optimize the use of Free Shipping, Vouchers, and Discounts to enhance sales growth on Shopee, thereby improving their competitive position in the e-commerce landscape.